Determinação simultânea de agrotóxicos e micotoxinas em fitoterápicos: Validação e aplicação de métodos multirresíduo empregando LC-MS/MS - Fontana, Marlos Eduardo Zorzella (2023)
The use of herbal medicines has increased significantly, but the presence of pesticide residues as well as the presence of mycotoxins have generated constant discussion and concern on the part of regulatory agencies. The development of analytical methods for the determination of pesticides and mycotoxins in medicinal plants is a great challenge, due to the substances naturally present in plants. In this study, QuEChERS was optimized followed by analysis by liquid chromatography coupled with sequential mass spectrometry for simultaneous determination of pesticides and mycotoxins in Melissa officinalis and Malva Sylvestris. The final method was validated according to SANTE/11312/2021 and consists of a variation of the QuEChERS method. In a 50 mL Falcon tube, 12 and 14 g of slurry were weighed. Then, 10 mL of acetonitrile 1% formic acid (v/v) containing the procedure's internal standard were added. The tubes were shaken on a mechanical shaker for 1 min. Then, 4 g of magnesium sulfate and 1 g of sodium chloride were added, and the samples were shaken again for 1 minute. The extracts were centrifuged, and 1 mL of the supernatant was quantitatively transferred to a dispersive clean-up kit containing a mixture of 25 mg PSA, 7.5 mg GCB and 150 mg MgSO4. The tubes were homogenized in vortex for 1 min and centrifuged again and 0.5 mL of extract was transferred to a vial and diluted with 0.5 mL of acetonitrile/water (1:1, v/v) containing the instrument's internal standard. The quantification limit ranged from 2 to 500 μg kg-1. Although some analytes still exhibited analytical signal suppression due to considerable matrix effect, an adequate linear range for matrix-paired calibration standards was achieved with adequate method performance due to the resolution of the mass spectrometer used. In all, 146 pesticides and 11 mycotoxins were validated for Melissa officinalis and 144 and 9 for Malva sylvestris. Commercial samples were analyzed and no residue above the detection limit was found, showing the quality of products marketed in the state of Rio Grande do Sul.